Early and geophysical validation of METOP / IASI water vapour measurements in the tropical upper troposphere and lower stratosphere, PI 3051 - Pommereau, J. P.; Durry, G.; Hauchecorne, A.; Held, G.; Calheiros, R. V.; Yushkov, V. (My University, 2006)
The proposal is dedicated to the validation of METOP / IASI water vapour measurements in the tropical tropopause layer where air enters the stratosphere by still debated processes and for the study of which very little reliable data exist. The initial proposal split in three parts: i) the comparison of IASI measurements to balloon, sondes and high altitude aircraft measurements in July-August 2006 in West Africa during a SCOUT-AMMA campaign part of the SCOUT-O3 Integrated Project of the European Commission; ii) the comparison of a large number of water vapour profiles in the 5-25 km altitude range anticipated from circumnavigating long duration balloons during a further SCOUT-Equatorial campaign in autumn 2007 in Brazil, and iii) a statistical comparison with year round water vapour soundings in Brazil using the Russian FLASH Lyman alpha instrument operated by the IPMet in Bauru, Brazil. After thorough validation the proposal is to use the IASI data for exploring the seasonal and inter-annual variations of water vapour concentration in the TTL.